Immunostimulation of Asian elephant (Elephas maximus) blood cells by parapoxvirus ovis and CpG motif-containing bacterial plasmid DNA upregulates innate immune gene expression - Haycock, Jonathan; Maehr, Tanja; Dastjerdi, Akbar; Steinbach, Falko (Frontiers in Immunology, 2024)
The immune system of Asian elephants (Elephas maximus) is poorly studied, compared to that of livestock, rodents or humans. The innate immune response has become a focus of interest in relation to Elephant endotheliotropic herpesviruses (EEHVs). EEHVs cause a fatal hemorrhagic disease (EEHV-HD) and are a significant threat to captive Asian elephant populations worldwide. Similar to other herpesvirus infections, nearly all animals become infected, but only some develop disease. As progression to EEHV-HD is often acute, a robust innate immune response is crucial to control EEHV infections. This is invariably true of the host in the first instance, but it can also potentially be modulated by intervention strategies. Here, two immunostimulant veterinary medicinal products, authorized for use in domestic species, were tested for their ability to induce innate anti-viral immune responses in Asian elephant blood cells. Sequence data were obtained for a range of previously unidentified Asian elephant immune genes, including C-X-C motif chemokine ligand 10 (CXCL10), interferon stimulated gene 15 (ISG15) and myxovirus GTPase 1 (Mx1), and were employed in the design of species-specific qPCR assays. These assays were subsequently used in analyses to determine fold changes in gene expression over a period of 24 hours. This study demonstrates that both immunostimulant medications are capable of inducing significant innate anti-viral immune responses which suggests that both could be beneficial in controlling EEHV infections in Asian elephants.